Prevalence of clinical and subclinical mastitis and its distribution pattern in the udder quarter of dairy cows at KPBSU Lembang, West Java - Debby Fadhilah Pazra; Kenedy Putra; Muhammad Najia Dinulloh; Fathul Bahri (Jurnal Ternak, 2026)
Mastitis is a major disease in dairy cattle that significantly impacts milk production and quality and causes economic losses in the livestock industry. This study aimed to analyze the prevalence of clinical and subclinical mastitis and its distribution patterns in udder quarters of dairy cows at the North Bandung Cattle Breeders Cooperative (KPSBU) in Lembang, West Java. This cross-sectional study included 100 lactating Holstein Friesian dairy cows with a total of 400 udder quarters from five villages. Subclinical mastitis was detected using the California Mastitis Test (CMT), and clinical mastitis data were obtained from livestock recordings in 2025. Data analysis was conducted descriptively to calculate the prevalence and distribution patterns of diseases. The results showed that the prevalence of subclinical mastitis at the cow level was 73%, whereas that of clinical mastitis was 38.88%. At the udder quarter level, the prevalence of subclinical mastitis reached 62%, with a higher distribution in the rear quarter (66%) than in the front quarter (58%). The highest prevalence was found in the right rear quarter (70 %), followed by the left rear quarter (62 %). The distribution pattern of mastitis showed that the incidence of the disease was uneven across the udder quarters and tended to be higher in the hindquarter, especially on the right side. Furthermore, the higher prevalence of subclinical mastitis compared to clinical mastitis reflects the tip-of-the-icebergphenomenon, where most cases go undetected clinically. In conclusion, the prevalence of mastitis in dairy cows at the Lembang Dairy Farm (KPSBU) was relatively high, especially subclinical mastitis, with a dominant distribution in the rear quarter, particularly the right rear quarter. Therefore, improved milking hygiene, early detection, and udder-based control strategies are needed to reduce the incidence of mastitis and increase dairy cow productivity.